Mass training: Versus intensive training in middle distance running - Enoksen, E.; Vik, B.; Gjerset, A. (2001)
In this study we have compared mass training versus intensive training in the development of aerobic endurance in Norwegian male middle-distance runners after a 10 week long training period. 26 athletes on a moderate to high national level, took part in the study. Two runners were matched against each other on the basis of their level of performance, their training background and their test results. The two runners were then assigned by chance to follow either the mass training model (M-group) or the intensive training model (I-group). The training period followed after a period of 12 weeks basic aerobic training. To measure the training effect of aerobic endurance, maximal oxygen uptake (VO2max), efficiency of running, level of anaerobic threshold (AT), and performance test on the treadmill with the running speed equivalent to100% of VO2max were all tested before and after the training period. The results show that the maximal oxygen uptake increased from 69.8 to 71.5ml?kg-1· min-1 for the I-group. The M-group had declining values, from 69.9 to 69.2 ml?kg -1?min-1, but this is due to weight gaining. The I-group achieved a significant improvement in their efficiency of running with all six sub-maximum running velocities, measured as declination in % of VO2max (p< 0.05). The I-group had an average declination of 4.4 %, while the M-group had a 2.1% declination. The anaerobic threshold speed (VAT) increased in both groups (I-group - 0.7km?t-1 and M-group 0.4km?t-1). The performance test shows that the I-group made 456 m (1.38 min) and the M-group 273 m (54 seconds) in progress.